Weighted composite analysis and its application: an example using ENSO and geopotential height. (17th October 2017) - Xie, Zhiang; Duan, Anmin; Tian, Qun
Abstract : Performance counts of the signal to noise ratio for weighted composite analysis (WCA) and traditional composite analysis (CA) in various sample size of CA and deviation ratio of noise over signal. "All" represents using all samples corresponding to positive index event. Abstract: The arbitrariness of composite analysis due to criterion of defining positive and negative events is an unsolved problem. To deal with it, a new method based on the covariance and defined as weighted composite analysis was developed in this study. Two ideal cases reveal that the new method can eliminate noise more effectively in small sample size, and has a higher signal to noise ratio than the traditional method in some cases. And a real case on the relationship between ENSO and geopotential height over East Asia in summer indicates that the new method shows some similar features with composite analyses, but can effectually avoid some inappropriate conclusions. It therefore provides an alternative approach to investigate linkages between different variables.